Comparison of Aortic Collagen Fiber Angle Distribution in Mouse Models of Atherosclerosis Using Second-Harmonic Generation (SHG) Microscopy. (7th January 2016) - Watson, Shana R.; Liu, Piaomu; Peña, Edsel A.; Sutton, Michael A.; Eberth, John F.; Lessner, Susan M.
Abstract: Characterization of collagen fiber angle distribution throughout the blood vessel wall provides insight into the mechanical behavior of healthy and diseased arteries and their capacity to remodel. Atherosclerotic plaque contributes to the overall mechanical behavior, yet little is known experimentally about how collagen fiber orientation is influenced by atherogenesis. We hypothesized that atherosclerotic lesion development, and the factors contributing to lesion development, leads to a shift in collagen fiber angles within the aorta. Second-harmonic generation microscopy was used to visualize the three-dimensional organization of collagen throughout the aortic wall and to examine structural differences in mice maintained on high-fat Western diet versus age-matched chow diet mice in a model of atherosclerosis. Image analysis was performed on thoracic and abdominal sections of the aorta from each mouse to determine fiber orientation, with the circumferential (0°) and blood flow directions (axial ±90°) as the two reference points. All measurements were used in a multiple regression analysis to determine the factors having a significant influence on mean collagen fiber angle. We found that mean absolute angle of collagen fibers is 43° lower in Western diet mice compared with chow diet mice. Mice on a chow diet have a mean collagen fiber angle of ±63°, whereas mice on a Western diet have a more circumferential fiber orientation (~20°). This apparent shift in absolute angle coincides with the development of extensive aortic atherosclerosis, suggesting that atherosclerotic factors contribute to collagen fiber angle orientation.